Acoustic performance study of lecture room during learning activities and rainfall at higher education institution - Tahir, Nor Suhaila; Rahmat, Muhamad Hanafi; Mohd Zawi, Mohammad Khidir; Abdul Wahab, Izudinshah; Abdul Salam, Nur Nasuha; Abdul Aziz, Hazri; Deraman, Rafikullah; Abdullah, Abd.Halid; Nagapan, Sasitharan; Tong, Yean Ghing; Abas, Nor Haslinda; Hasmori, Muhammad Fikri (Politeknik, 2018)
Noise pollution has become one of the significant world problems along with air pollution and water pollution. Previous research had found that the ability to find quiet times and places are essential to support knowledge work. The main source of noise pollution in the educational institution are traffic noise, community noise and industrial noise. Besides, the usage of the metal deck as roofing system at lecture room may also affecting the acoustic performance level during rainy days. This is because the rain noise is often becomes unpleasant problems that disturb learning activities caused from the noise produced by rainfall when it hit the surface of the metal deck roof. Experimental studies were undertaken to investigate the acoustic performance in a lecture room (E15-BK2) located at block E15 of Universiti Tun Hussein Onn Malaysia. The comfort noise level for the learning space should not exceed 55 dBa for the learning spaces to achieve the effectiveness of learning process. This study will be focusing on obtaining data of Sound Pressure Level in lecture room with learning activities and no learning activities by using Sound Level Meter (RS-322). The result had shown that the noise recorded at the lecture room during learning activities, no learning activities and during rainfall had exceeded the requirement set by Department of Environment Malaysia which is 55 dBA and the acoustic performance in the lecture is not in the suitable position for the learning process. Therefore, some adjustment and renovation should be done to the lecture room so that the Sound Pressure Level (SPL) should fall within the accepted standard.